11. Post-anoxic status epilepticus: The impact of medical treatment on outcome. A single center experience. Issue 12 (December 2016) - Lettieri, C.; Devigili, G.; Pauletto, G.; Rinaldo, S.; Coccolo, D.; Cipolat, V.; Budai, R.; Eleopra, R.
Abstract : In post-anoxic comatose patients, SE is used to be considered a strong poor outcome predictor. The aim of our study was to assess, retrospectively, the outcome of SE after pharmacological treatment with antiepileptic (AEDs) and/or anesthetic drugs in a series of post-anoxic comatose patients and to verify any correlation with other outcome predictors. We retrospectively analyzed data collected from 60 patients affected by hypoxic encephalopathy. Demographic data, SE subtype and duration, coma scale scores (FOUR scale), time of return of spontaneous circulation (ROSC), presence of cortical SSEP (N20), presence of pupillary light reflex, pharmacological treatment and clinical outcome according to Glasgow Outcome Scale (GOS) were evaluated. Finally we performed a statistical analysis by means of a logistic regression. A total of 17 patients showed an EEG pattern consistent to SE. Of them, 12 patients were treated with antiepileptic/anesthetic drugs: 7 patients showed a good outcome (GOS > 2). We found a statistically significant correlation with preserved N20 and anesthetic drugs. Based on our results, we can argue that in post-anoxic encephalopathy, SE doesn't always correlate with poor outcome especially when other more robust prognostic factors, such as cortical SSEP, are preserved. In such patients, an aggressive antiepileptic treatment could modify prognosis.